3 va rog dau subscribe si coroana
Anexe:
Răspunsuri la întrebare
Răspuns de
2
a)
(2x-3)+(6x-10)+(13-7x)=
2x-3+6x-10+13-7x=
(2x+6x-7x)+(-3-10+13)=
x
b)
-12-(4x²+3)-x²=
-12-4x²-3-x²=
(-12-3)+(-4x²+x²)=
-15-5x²
c)
18-(7x-5)+(23x-21)=
18-7x+5+23x-21=
(18+5-21)+(-7x+23x)=
2+16x
d)
(-5+a-2x)-(6x+20-5a)=
-5+a-2x-6x-20+5a=
(-5-20)+(a+5a)+(-2x-6x)=
-25+6a-8x
(2x-3)+(6x-10)+(13-7x)=
2x-3+6x-10+13-7x=
(2x+6x-7x)+(-3-10+13)=
x
b)
-12-(4x²+3)-x²=
-12-4x²-3-x²=
(-12-3)+(-4x²+x²)=
-15-5x²
c)
18-(7x-5)+(23x-21)=
18-7x+5+23x-21=
(18+5-21)+(-7x+23x)=
2+16x
d)
(-5+a-2x)-(6x+20-5a)=
-5+a-2x-6x-20+5a=
(-5-20)+(a+5a)+(-2x-6x)=
-25+6a-8x
Ciulisnariku:
multumesc mult
Alte întrebări interesante
Matematică,
8 ani în urmă
Arte,
8 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă